Gender in South Asia : social imagination and constructed realities - Channa, Subhadra, 1951- (Cambridge : Cambridge University Press, 2018)
"Discusses gender in terms of models generalizing upon received wisdom from historical and cultural sources and lived realities"--Provided by publisher.
Introduction -- Colonial India and the construction of upper-caste/class women -- Elite women: education and emergence of feminism -- Work and gender relations of a low-caste group in urban Delhi -- Globalization and the emerging gender issues in India -- Conclusion: redefining the feminine.
Includes bibliographical references (pages 210-222) and index.
ENH
Keywords: Women -- India -- Social conditions; Women -- India -- History; Feminism -- India; English language